Students’ Perceptions of Improving English Speaking Skills Through the Youtube Channel “English Singsing” - Nida Salsabilah; Ardya Arzahrin; Sefani Putri; Padia Kamila (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
Speaking English fluently is one of the key components of teaching a language. One of the useful technology tools for raising students' speaking skills is YouTube. Because there is currently not enough research on the effectiveness of the English Singsing YouTube channel in enhancing the speaking skills of learners, this study was carried out. The study aims to explore students' perceptions of improving English speaking Skills through the YouTube Channel “English Singsing”. The design of this study is qualitative. A fourth-semester English student is the study's subject. 14 question questionnaire used as part of the data collection method was modified from Saraswati (2019). The results show that students believe that YouTube is a useful tool for language learning and helps them improve their speaking skills. They believe that the